Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Kemampuan Berkomunikasi Dalam Pembelajaran di SD Negeri No. 104274 Pematang Kasih Kecamatan Pantai Cermin Kabupatan Serdang Berdagai - Sitepu, Nur Alfina Sari; OK, Azizah Hanum (Jurnal Kependidikan Islam, 2023)
In the learning process is not only related to knowledge but communication in the world of education is also very important. Every learning activity is synonymous with communicating, therefore a teacher has an important role in developing students' communication skills in learning. So there needs to be an effort made by PAI teachers at SD Negeri No. 104274 Pematang Kasih to improve students' communication skills to make it easier for students to understand the learning material delivered. The efforts made are in the form of providing good communication examples, guiding students when asking questions, making presentations in discussion activities, using question and answer methods, using active learning strategies and doing habituation. This research uses qualitative methods with a phenomenological approach. The purpose of the efforts made is to create effective communication and a pleasant learning atmosphere.